A validation study of the double standard scale and the rape supportive attitude scale in Brazilian women - Juan Carlos Sierra (Universidad de San Buenaventura, 2009)
The need to improve measurement in research of violence against women has been recognized. The purpose of this study was introduced first psychometric data of two questionnaires assessing sexist attitudes on Brazilian women: Double Standard Scale (DSS) and Rape Supportive Attitude Scale (RSAS). Both scales were administered in two women samples (N = 300; N = 500). In accordance with previous research, the findings reproduced the single-factor structure on each scale. Reliability estimation through Cronbach s alpha evidenced satisfactory internal consistency values for each scale. Finally, evidence that supports the measurement validity of the DSS and the RSAS was also provided.